Immobilization of the Lipase B from Candida antarctica on Urban Solid Waste - Llerena Suster, Carlos Rafael (2023)
The adsorption of the lipase B from Candida antarctica (CALB) over polyethylene terephthalate (PET), polypropylene (PP), and derivatives, abundant components of urban solid waste (USW),was investigated. The characterization of the supports and biocatalysts synthesized by SEM-EDS and FTIR is presented. Two immobilization strategies were evaluated, conventional and total adsorption. The adsorbed protein was determined by Bradford and through high-resolution inductively coupled plasma atomic emission spectroscopy (ICP-AES). In this sense, the adsorption of CALB in all the proposed supports was evidenced, obtaining the highest protein loads in bis-(2-hydroxyethyl) terephthalate (BHET). Subsequently, the biocatalysts were applied to the esterification of rac-ibuprofen with ethanol. CALB immobilized in BHET showed remarkable activity, achieving conversions of 30%. In this context, immobilization on this support was optimized, studying the addition of sorbitol-glycerol. Thus, in the presence of 0.91 g of polyols, a catalyst with a protein load of 33.3 mg·g−1 was obtained, achieving productivity of 0.298 mmol min−1 mg−1 . Additionally, no differences were found when using BHET from USW bottles of various colors. This research shows the potential of materials derived from PET as enzymatic supports, unreported materials, that we can use as tools to achieve sustainable biotechnological applications.